Analisis Distribusi Dosis Radiasi terhadap Perencanaan Radioterapi Menggunakan Metode Segmentasi Citra pada Kasus Tumor Otak dengan Teknik Intensity Modulated Radiation Therapy (IMRT) - Izza Wahyu Saputri Saputri; Ida Bagus Made Suryatika; Cory Amelia; I Nengah Sandi; Made Sumadiyasa; I Gusti Agung Widagda; Rozi Irhas (Universitas Hamzanwadi, 2025)
A study has been conducted on the effect of the number of segments on the radiation dose distribution of photon beams in brain tumor cases using the Intensity Modulated Radiation Therapy (IMRT) technique. This study used 20 primary data and 10 secondary data from brain tumor patients with 6 MV photon beams and a total dose of 6000 cGy. Calculations were performed by analyzing the Homogeneity Index (HI) and Conformity Index (CI) values as well as the radiation dose to the Organs at Risk (OAR), followed by statistical testing. Based on the conducted research, the results showed that HI and CI values for 5, 10, and 15 segments were different. For example, the HI value for 5 segments was more homogeneous, approaching 0, and the CI value for 10 segments was closer to 1, which indicates a better match with the PTV shape. The average maximum dose distribution for OARs with 5 segments in the brainstem, chiasma, left eye, right eye, left lens, and right lens were 4541.9 cGy, 3893.8 cGy, 2754.2 cGy, 2516.1 cGy, 740.8 cGy, and 628.0 cGy, respectively. With 10 segments, the doses for these OARs were 4104.2 cGy, 3633.9 cGy, 2583.9 cGy, 3124.2 cGy, 710.5 cGy, and 625.5 cGy, respectively. With 15 segments, the doses for the same OARs were 4123.0 cGy, 3956.2 cGy, 2753.3 cGy, 2433.7 cGy, 667.7 cGy, and 547.8 cGy, respectively. All maximum dose distributions for the OARs received by the patients were still within the tolerance limits stated in the Radiation Oncology A Question-Based Review 2nd Edition.